A critical analysis of the riparian rights of water abstractors within England and Wales. - Evans, B; Howsam, Peter (Lawtext Publishing, 2005)
This analysis explores how traditional riparian rights to abstract water have developed into English law. How the balance between private rights and state control is managed by modern society is examined. The main tool has been the use of exemptions. The practicalities faced by the regulator in enforcing the legislation are discussed.